Four new species of the genus Trichodromeus Luze, 1903 from Nepal and Pakistan (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) - Shavrin, Alexey V. (Zootaxa, 2021)
Four new species of the genus Trichodromeus Luze, 1903 are described and illustrated: T. acutipenis Shavrin, sp.n., T. jaegeri Shavrin, sp.n. and T. kaliyuga Shavrin, sp.n. from Nepal, and T. trilobatus Shavrin, sp.n. from Pakistan (Azad Kashmir). A key to species and distribution maps for all Nepalese species are provided. The genus is recorded from Nepal for the first time.